Are we prepared for the next influenza pandemic? Lessons from modelling different preparedness policies against four pandemic scenarios. (21st November 2019) - Panovska-Griffiths, Jasmina; Grieco, Luca; van Leeuwen, Edwin; Baguelin, Marc; Pebody, Richard; Utley, Martin
Highlights: We characterised the four past influenza pandemics by their transmissibility and infection-severity. We projected the benefits of different preparedness policy against the four historic influenza pandemics. Immunisation against pandemic influenza, in presence of effective antiviral drugs, does not have positive net-present value across all pandemic scenarios considered. In absence of effective antiviral drugs, vaccination was most beneficial if started sufficiently early and covered sufficiently large number of people. Comparing the two vaccine programmes, the responsive-purchase immunisation policy allowed a longer timeframe and lower coverage to attain the same benefit as the pre-purchase immunisation policy. Abstract: In the event of a novel influenza strain that is markedly different to the current strains circulating in humans, the population have little/no immunity and infection spreads quickly causing a global pandemic. Over the past century, there have been four major influenza pandemics: the 1918 pandemic ("Spanish Flu"), the 1957–58 pandemic (the "Asian Flu"), the 1967–68 pandemic (the "Hong Kong Flu") and the 2009 pandemic (the "Swine flu"). To inform planning against future pandemics, this paper investigates how different is the net-present value of employing pre-purchase and responsive- purchased vaccine programmes in presence and absence of anti-viral drugs to scenarios that resemble these historic influenza pandemics. Using the existing literature and in discussions with policy decision makers in the UK, we first characterised the four past influenza pandemics by their transmissibility and infection-severity. For these combinations of parameters, we then projected the net-present value of employing pre-purchase vaccine (PPV) and responsive-purchase vaccine (RPV) programmes in presence and absence of anti-viral drugs. To differentiate between PPV and RPV policies, we changed the vaccine effectiveness value and the time to when the vaccine is first available. Our results are "heat-map" graphs displaying the benefits of different strategies in pandemic scenarios that resemble historic influenza pandemics. Our results suggest that immunisation with either PPV or RPV in presence of a stockpile of effective antiviral drugs, does not have positive net-present value for all of the pandemic scenarios considered. In contrast, in the absence of effective antivirals, both PPV and RPV policies have positive net-present value across all the pandemic scenarios. Moreover, in all considered circumstances, vaccination was most beneficial if started sufficiently early and covered sufficiently large number of people. When comparing the two vaccine programmes, the RPV policy allowed a longer timeframe and lower coverage to attain the same benefit as the PPV policy. Our findings suggest that responsive-purchase vaccination policy has a bigger window of positive net-present value when employed against each of the historic influenza pandemic strains but needs to be rapidly available to maximise benefit. This is important for future planning as it suggests that future preparedness policies may wish to consider utilising timely (i.e. responsive-purchased) vaccines against emerging influenza pandemics.